2002
DOI: 10.1128/jvi.76.5.2306-2315.2002
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Feline Leukemia Virus-Specific Cytotoxic T Lymphocytes: Correlation with Recovery from Infection

Abstract: Feline leukemia virus (FeLV) is a common naturally occurring gammaretrovirus of domestic cats that is associated with degenerative diseases of the hematopoietic system, immunodeficiency, and neoplasia. Although the majority of cats exposed to FeLV develop a transient infection and recover, a proportion of cats become persistently viremic and many subsequently develop fatal diseases. To define the dominant host immune effector mechanisms responsible for the outcome of infection, we studied the longitudinal chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
3

Year Published

2004
2004
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 41 publications
6
51
0
3
Order By: Relevance
“…The finding of previously covert viral DNA in some cats which ostensibly totally resisted FeLV infection was not restricted to FeLV-61E-A, as other investigators found a similar phenomenon in cats challenged with the FeLV-A/Glasgow-1 Flynn et al, 2002;Tandon et al, 2005;Cattori et al, 2006;Gomes-Keller et al, 2006a;Gomes-Keller et al, 2006b;. It remained unknown, however, whether the viral DNA we detected by our qPCR assay represented intact, replication-competent provirus or replication-defective viral DNA sequences.…”
Section: Introductionmentioning
confidence: 39%
See 2 more Smart Citations
“…The finding of previously covert viral DNA in some cats which ostensibly totally resisted FeLV infection was not restricted to FeLV-61E-A, as other investigators found a similar phenomenon in cats challenged with the FeLV-A/Glasgow-1 Flynn et al, 2002;Tandon et al, 2005;Cattori et al, 2006;Gomes-Keller et al, 2006a;Gomes-Keller et al, 2006b;. It remained unknown, however, whether the viral DNA we detected by our qPCR assay represented intact, replication-competent provirus or replication-defective viral DNA sequences.…”
Section: Introductionmentioning
confidence: 39%
“…Application of qPCR to detect FeLV DNA in conjunction with p27 capsid capture ELISA has resulted in diagnostic sensitivity of 100% Flynn et al, 2002;Tandon et al, 2005;Torres et al, 2005;Cattori et al, 2006;Gomes-Keller et al, 2006a;Gomes-Keller et al, 2006b;Hofmann-Lehmann et al, 2006). In addition we, and others, found animals in which viral DNA was detected in the absence of detectable antigenemia, demonstrating that qPCR sensitivity was greater than p27 ELISA and that viral DNA burden was an accurate predictor of FeLV infection outcome.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Se o animal não desenvolve imunidade adequada, o vírus é disseminado sistemicamente por linfócitos e monócitos. A antigenemia/viremia é transiente, pois é detectável por cerca de três a seis semanas, ocorrendo completa eliminação do vírus após esse período (LUTZ et al, 1980;FLYNN et al, 2000;FLYNN et al, 2002); infecção latente -O animal apresenta antigenemia/ viremia por mais de três semanas e ocorre infecção de células da medula óssea (ROJKO et al, 1979;HARTMANN, 2006). Dentro de meses, o animal desenvolve uma resposta imune capaz de eliminar a antigenemia/viremia, mas o DNA proviral está presente nas células precursoras da medula.…”
Section: Patogenia Do Felv Com O Emprego De Técnicas Convencionais Deunclassified
“…O teste detecta animais positivos a partir da quarta semana após infecção (JARRET et al, 1982;FLYNN et al, 2002) e é recomendado como teste de triagem (LEVY et al, 2008;LUTZ et al, 2009).…”
Section: Introductionunclassified